Stigmatization, life satisfaction, and its associated factors of childfree women: A scoping review - Suhariyati, Suhariyati; Rahmawati, Shinta Alifiana; Ubudiyah, Masunatul (Universitas Airlangga, 2025)
Introduction: Having children during marriage is a way to preserve the family lineage. To be childfree leads to negative stigma from society and even one's own family. However, not all couples want to have children, some of them choose to be childfree. Objective: This study aimed to review literature about the perspective of women who choose to be childfree. Methods: The literature search about being childfree used electronic databases, namely Scopus and PubMed, with the keywords “childfree,